Inter-joint coordination in producing kicking velocity of taekwondo kicks - Kim, Y. K.; Kim, Y. H.; Im, S. J. (Journal of Sports Science & Medicine, 2011)
The purpose of this study was to investigate joint kinematics of the kicking leg in Taekwondo and to examine the role of inter-joint coordination of the leg in producing the kicking velocity. A new inter-joint coordination index that encompasses three- dimensional hip and knee motions, was defined and applied to the joint kinematic results. Twelve elite Taekwondo athletes participated in this study and performed the back kick, thrashing kick, turning-back kick and roundhouse kick. Our results indicate that the back kick utilized a combination of hip and knee extension to produce the kicking velocity, and was characterized by a pushlike movement. The thrashing kick and turning-back kick utilized a greater degree of hip abduction than the roundhouse kick and back kick, and included complicated knee motions. The new index successfully categorized the thrashing kick and turning-back kick into a push-throw continuum, indicating a change from negative index (opposite direction) to positive index (same direction) of hip and knee motions at the end of the movement. This strategy of push-throw continuum increases the kicking velocity at the moment of impact by applying a throwlike movement pattern.